Film-cooling hole optimization and experimental validation considering the lateral pressure gradient - Zhang, Hao; Gou, Jinlan; Yin, Peng; Su, Xinrong; Yuan, Xin (Frontiers in Mechanical Engineering, 2023)
The flow in the turbine endwall region consists of the complicated secondary flow structures driven by the lateral pressure gradient, which heavily affects the performance of the film cooling. In this work, the film cooling hole design optimization is performed considering the existence of the lateral pressure gradient in the real flow environment. Results have shown that optimal film cooling hole design is heavily influenced by the lateral pressure gradient in the endwall region, especially the compound angle design is clearly different from the flat plate flow environment. The optimization results are further validated with experiments using the Pressure Sensitive Paint (PSP) technique, and the film cooling performance is shown to be improved by 42.9%. This work demonstrates the importance of considering the real flow environment in the film cooling hole design, and also can provide guidance to the film cooling hole design in the endwall region.